‘Buy Luxury’: Adapting the SHIFT Framework to Explore the Psychological Facets Enabling Consumers for Sustainable Luxury Consumption - Giri, Arunangshu; Biswas, Wendrila; Salo, Jari (Indian Journal of Marketing, 2022)
This era of the global market is witnessing a new look for luxury products and services. There has been an accelerating shift in consumption patterns and consumer preferences for sustainable luxury products. Moreover, the COVID - 19 pandemic acted as a catalyst for changes in consumer behavior and adapting to a new way of living. Consumer trends have revealed that sustainability has become a key consideration in varied consumer segments when making their purchase decisions. Consumers’ drive for environmental stability, social responsibility, and ethical practices has well been reflected in their lifestyles today. Thus, companies are re-evaluating their products’ sustainability credentials and adopting a new paradigm of value creation to meet the changing psychological approach of consumers. This short communication delved into consumers’ psychological aspects that drive momentum towards sustainable luxury consumption. Here, the SHIFT framework (White et al., 2019) was adopted to highlight the subtle psychological facets of consumers that trigger them to embrace sustainable luxury consumption. The perspective presented a conceptual framework that indicated various psychological facets (atypicality, social desirability, life changes, need for uniqueness, self benefits, sense of accomplishment, pro-environment nature, personal experience of others, and consideration of legacy) of a consumer, which influence sustainable luxury consumption.